Decay time dynamics of red and blue luminescence of surface-functionalized silicon quantum dots - Joo, B.S.; Gu, M.; Han, J.; Jung, N.; Kim, S.; Park, D.-W.; Han, M. (Elsevier B.V., 2021)
Controlling the emission wavelength by the quantum confinement or the size effect of silicon quantum dots (Si QDs) has a limitation in that it can be only approximately 600 nm or above. To overcome this limitation, in the recent decade, numerous studies have been conducted for reproducing the entire visible range from blue to red from Si QDs by their surface functionalization. In this study, we fabricated alkyl- and amine-passivated Si QDs and investigated their emission mechanism following surface functionalization. We interpreted the emission mechanism of the surface-functionalized Si QDs by combined experimental analysis of the decay time dynamics and density functional theory-based model calculation of the highest occupied molecular orbital-lowest unoccupied molecular orbital electronic structures. Our comprehensive studies could provide insight into the debated problems of the luminescence mechanism of surface-functionalized Si QDs. ？ 2021 Elsevier B.V.
Keywords: Density functional theory; Electronic structure; Luminescence; Molecular orbitals; Nanocrystals; Semiconductor quantum dots; Silicon; Blue luminescence; Decay time; Emission mechanism; Emission wavelength; Functionalized; Luminescence properties; Red luminescence; Silicon quantum dots; Surface Functionalization; Time dynamic; Charge transfer